Diagnosis and management of subcutaneous implantable cardioverter‐defibrillator infections based on process mapping. Issue 9 (23rd April 2020) - Baddour, Larry M.; Weiss, Raul; Mark, George E.; El‐Chami, Mikhael F.; Biffi, Mauro; Probst, Vincent; Lambiase, Pier D.; Miller, Marc A.; McClernon, Timothy; Hansen, Linda K.; Knight, Bradley P.
Abstract: Background: Infection is a well‐recognized complication of cardiovascular implantable electronic device (CIED) implantation, including the more recently available subcutaneous implantable cardioverter‐defibrillator (S‐ICD). Although the AHA/ACC/HRS guidelines include recommendations for S‐ICD use, currently there are no clinical trial data that address the diagnosis and management of S‐ICD infections. Therefore, an expert panel was convened to develop consensus on these topics. Methods: A process mapping methodology was used to achieve a primary goal – the development of consensus on the diagnosis and management of S‐ICD infections. Two face‐to‐face meetings of panel experts were conducted to recommend useful information to clinicians in individual patient management of S‐ICD infections. Results: Panel consensus of a stepwise approach in the diagnosis and management was developed to provide guidance in individual patient management. Conclusion: Achieving expert panel consensus by process mapping methodology in S‐ICD infection diagnosis and management was attainable, and the results should be helpful in individual patient management.